Drying and Valorisation of Food Processing Waste - Chong, Chien Hwa; Rafeah, Wahi; Choo, Chee Ming; Chew, Shee Jia; Mackingsley Kushan, Dassanayake (CRC Press, 2024)
Drying and Valorisation of Food Processing Waste is a comprehensive guide that delves into the crucial role of advanced drying technologies in mitigating the issue of food waste. This book evaluates the current research, technologies, and methodologies in food waste processing and valorisation, highlighting the challenges and opportunities that exist in this field.